Discourse of art in poetry Volodymyr Samiilenko (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article deals with the peculiarities of the content and implementation of artistic discourse in the poetic works of art by famous Ukrainian author limits nineteenth and twentieth centuries Volodymyr Samiilenko. It is noted that improvements in the Ukrainian poet occupies the context of this day a special place, as in the poetic works of the writer uniquely combines elements of populist and modernist correctly interpreting the nature of art and its place in human life. In the article the basic art images relevant to the discourse of art in his poetry. In particular, it insults the song, muse, Ukraine, poetic speech. In poetry Volodymyr Samiilenko used as satirical and humorous images are tailored respective artistic genres. On the material analysis of different poetic works of the author have been allocated the basic elements of horizontal and vertical paradigm of artistic vision of the poet. Outlined that the center of the art world, which is presented in the artistic heritage of Volodymyr Samiilenko, there is a person, artistically interpreted in conjunction intellectual and sensory principles. This approach peculiar to Ukrainian culture, history and literary discourse limits the nineteenth and twentieth centuries.
Keywords: discourse; art; poetry; populism; modernism; artistic image